PERANCANGAN MESIN PEMERAS SANTAN DENGAN SISTEM SPINNER - Ramdani, Rifki; Kadarismansyah (Universitas Nusa Putra, 2021)
Coconut plants are very abundant natural resources and useful for humans. One of the benefits of coconut plants is: coconut flesh which is the raw material for coconut milk which is generally used as food preparations. In general, the process of squeezing coconut milk is still using a manual extortion process, so it requires energy and time which is quite long. To overcome this, it is necessary to design a machine efficient coconut milk squeezer, this machine is designed using materials that economical so that it can be reached by all people, especially those who have a culinary business. This coconut milk squeezer works on the principle of the system rotate, the grated coconut meat is placed in a tube in the machine, at that time the coconut meat will be rotated at high speed so that The liquid coconut milk contained in the coconut meat is separated from the coconut meat. Motorcycle the driving force used is an electric motor, the power on the electric motor will transmitted from the rotation of the pully motor through the v-belt to the pully and the shaft which moved. The extortion process is carried out by pressing the on button so that the tube will rotate automatically. Coconut meat in the tube will not be damaged because there is no pressing process when the engine is rotating.